Victory Gin Lane. Starvation and Beverages in Orwell’s Nineteen Eighty-Four (Altre Modernità, 2015)
Gin is an ubiquitous presence in the domestic and urban scenery of Nineteen Eighty-Four (1949). For a population mercilessly hungered, it represents a handy and cheap commodity item providing a fluid opportunity for social aggregation. Victory Gin, served “in handless chine mugs” (53), is part of the workers’ staple diet at the Ministry of Truth, and is sold “at ten cents the large nip” from the small bar (actually, “a mere hole in the wall”, 51) in the canteen; served with cloves, it is the “speciality” (79) of that disreputable place which is the Chestnut Tree Café, where Winston Smith once spotted three fallen-out-of-favor members of the Inner Party – Jones, Aaronson and Rutherford – drink it silently after their release from Oceania prison camps (79). As is typical of the fate of spirits in literature, gin also serves as self-medication and can fuel a kind of inner escapism. It is to make the world “look more cheerful” that Winston gulps it down “like a dose of medicine”, and only after the “shock” of swallowing it can he squeeze himself into his alcove and begin his diary (7); gin clears out Winston’s stomach (53), and is the ultima ratio against that prescient “dull ache” in his belly (105; 106) that originates after bumping into “the girl with dark hair” (later: Julia) one evening outside Mr. Charrington’s shop.